The Relevant of Sex Hormone Levels and Acne Grades in Patients with Acne Vulgaris: A Cross-Sectional Study in Beijing - Zhang R; Zhou L; Lv M; Yue N; Fei W; Wang L; Liu Z; Zhang J (Dove Medical Press, 2022)
Rui Zhang1 *, Lanhua Zhou2 *, Meiyu Lv,1 Na Yue,1 Wenting Fei,3 Linyuan Wang,3 Zhaolan Liu,1 Jianjun Zhang1 1School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 102488, People's Republic of China; 2Department of Dermatology, Beijing Jingcheng Skin Hospital, Beijing, 100192, People's Republic of China; 3School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing, 102488, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianjun Zhang, School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Liangxiang Town, Fangshan District, Beijing, 102488, People's Republic of China, Email zhangjianjun@bucm.edu.cnBackground: The tests of sex hormones play pivotal roles in the clinical diagnosis and treatment of acne vulgaris, but the majority of patients with acne vulgaris present regular sex hormone levels within the normal reference range.Objective: To determine the correlation among levels of sex hormones, ratio of androgen to estrogen and acne grades in patients with acne vulgaris.Methods: A cross-sectional study was applied to collect 693 patients with acne vulgaris. All samples were screened by cluster sampling among those who underwent tests of sex hormones at Beijing Jingcheng Skin Hospital from July 2021 to June 2022. A gender stratified analysis was performed to classify acne grades I-IV. Spearman correlation analysis was used to analyze the relationship between age, sex hormones, ratio of androgen to estrogen and acne grades, with multinomial logistic regression to analyze the association of sex hormones with acne grades in patients with acne.Results: (1) The testosterone levels were mostly within normal reference values for both males and females with varying degrees of acne. For females, the serum follicle-stimulating hormone, estradiol, progesterone, testosterone, and ratio of androgen to estrogen were significantly different between acne grades. For males, there were significant differences in serum estradiol, testosterone, and ratio of androgen to estrogen across acne grades. (2) The acne grade was negatively correlated with estradiol and positively correlated with the ratio of androgen to estrogen; the female acne grade was also negatively correlated with age and progesterone, but positively correlated with follicle-stimulating hormone. (3) Multivariate logistic regression analysis indicated that the ratio of androgen to estrogen was independently correlated with the grade of acne and that acne grade worsened as the ratio increased.Conclusion: The increase in the ratio of androgen to estrogen may aggravate the acne grade in patients with acne vulgaris.Keywords: acne vulgaris, sex hormones, testosterone, estradiol, ratio of androgen to estrogen